The Effects of Varieties Sources of Omega- 3 Fatty Acids on Diabetic Male Rats - Eman A. Al-Rekabi (Journal of Global Pharma Technology, 2016)
The aim of the present study was to investigate the effects of varieties sources of omega-3 on blood parameters, lipid profile and liver enzymes in diabetic male rats. Fish oil and flaxseed oil were used and the animals were maintained with (0.5ml/animal/day). The results indicated that the treatment of diabetic male rats with fish oil and flaxseed oil caused a significant increase (P<0.05) in Hb and PCV and caused a significant decrease (P<0.05) in WBC in compared with diabetic male rats. The results showed a significant decrease in cholesterol, triglycerides, low density lipoprotein (LDL), very low density lipoprotein (VLDL) and liver enzymes, whereas it explained a significant increase in high density lipoprotein (HDL) of  diabetic male rats treated with fish oil and flaxseed oil when compared with diabetic male rats. The study suggested that fish oil and flaxseed oil especially may be as antidiabetic.Keywords: Diabetic male rats; Omega-3; Fish Oil; Flaxseed Oil; Blood parameters; Lipid profile; Liver enzyme.